The Traces of Cinema in the Work of Manuel Rivas - Castro Otero, Salvador (Madrygal. Revista de Estudios Gallegos, 2019)
Cinema became the most popular form of narration of twentieth century. It not wonders, then, that this way of telling influenced other arts, especially literature. This work proposes a classification of the relationships between audiovisual texts and writings and it shows the characteristic features of the seventh art present in the literary and journalistic work of Manuel Rivas and, by extension, in other writers of the past century.